Thinking About America's Defense An Analytical Memoir - Kent, Glenn A. (RAND Corporation, 2008)
Lieutenant General Glenn A. Kent was a uniquely acute analyst and developerof American defense policy in the second half of the twentieth century. His33-year career in the Air Force was followed by more than 20 years as one ofthe leading analysts at RAND. This volume is not a memoir in the normalsense but rather a summary of the dozens of national security issues inwhich Glenn was personally engaged over the course of his career. Theseissues included creating the single integrated operational plan (SIOP),leading DoD's official assessment of strategic defenses in the 1960s,developing and analyzing strategic nuclear arms control agreements, helpingto bring new weapon systems to life, and many others. Each vignettedescribes the analytical frameworks and, where appropriate, the mathematicalformulas and charts that Glenn developed and applied to gain insights intothe issue at hand. The author also relates his roles in much of thebureaucratic pulling and hauling that occurred as issues were addressedwithin the government.